Virus-Free Sweet Potato Industry: Development Status and Production Suggestions - Ying Xu; Li-Xiang Wang; Chen Chen; Shao-Shan Ma; Rui Zhou; Ai-Sheng Xiong (Horticulturae)
Sweet potato (Ipomoea batatas L.) is an important food, feed, and industrial raw material and new energy crop. Its rich nutritional value and health effects are increasingly being recognized by consumers, and the demand is increasing. However, due to the continuous cultivation of sweet potato over many years, the degeneration of seedlings and the accumulation of viral diseases are important factors affecting the yield and quality of sweet potatoes. This article provides an overview and analysis of the types and hazards of sweet potato virus diseases, the advantages of virus-free sweet potatoes, the scale of virus-free sweet potato cultivation, sweet potato stem tip virus-free production technology, its development status, and the existing problems. Combined with the development of the sweet potato industry across China, relevant development suggestions are proposed to provide a reference for promoting the healthy, stable, sustainable, high-quality, and efficient development of the sweet potato industry.